2015
DOI: 10.4172/2161-0940.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Swallow Kinematics of a Person with Congenital Aglossia

Abstract: Objective: This research study explored movement of key processes during speech and swallow of a person with congenital aglossia. It expands upon earlier studies that found a high degree of intelligibility among listeners for expressive speech by the person with congenital aglossia and seeks to identify the dynamics through which the articulators accomplish this phenomenon.Methods: Positional movements of the mandible and hyoid bone and mylohyoid and tongue base for speech and swallow were compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The absence of the tongue was compensated for by the fact that the floor of the mouth (mylohyoid) and base of the tongue were hypertrophied and could independently and symmetrically be elevated to contact the palate during speech and swallow [18,19]. There was no evidence of hyper-or hypo-nasality as a resonatory characteristic [14,15].…”
Section: Subjectmentioning
confidence: 99%
See 3 more Smart Citations
“…The absence of the tongue was compensated for by the fact that the floor of the mouth (mylohyoid) and base of the tongue were hypertrophied and could independently and symmetrically be elevated to contact the palate during speech and swallow [18,19]. There was no evidence of hyper-or hypo-nasality as a resonatory characteristic [14,15].…”
Section: Subjectmentioning
confidence: 99%
“…Only 11 cases have been reported internationally [1][2][3][4][5][6][7][8][9][10][11] since it was first described systematically by De Jussieu in 1718 [12] whose original paper was investigated and described by Salles et al in 2016 [13]. McMicken and her co-authors [13][14][15][16][17][18][19][20] have reported extensively on research from cinefluorographic films and audio-visual (AV) recordings collected in 1986 on a 16-year-old female PwCA. This research included perception of vowel production [14], perception of consonant production [15], and cinefluorographic examination of articulation [16], in addition to current re-examination of the PwCA, now in her 40s, with electropalatography [17], videoflourography of articulatory movements of pseudo tongue, hyoid and mandible [18], and speech and swallowing kinematics [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, in 1986, one person with CA (PwCA) was identified, and became the participant of subsequent research based on cineradiographic films (CRFs), audio/ visual recordings, videoflouroscopy, electropalatography (EPG), taste testing, and in-vivo analysis that has provided a wealth of information regarding the adaptations in vocal tract resonance characteristics, modifications to articulatory processes, alternate neurological pathways to taste discrimination, and altered patterns of chewing and swallowing. Five previous manuscripts have detailed this research [4][5][6][7][8]. The current manuscript discusses an investigation into the production of the lingua-alveolar stop consonants, /t/ and /d/, produced by the PwCA and the specific anatomical and physiological properties and the kinematics involved in these intelligible articulatory productions.…”
Section: Introductionmentioning
confidence: 99%